Effect of biologic therapies on quality of life in severe asthma: Findings from the PRISM study - Hyo-In Rhyou, MD, PhD; Hyun-Kyoung Kim, MPH; Woo-Jung Song, MD, PhD; Sang Min Lee, MD, PhD; Sang-Ha Kim, MD, PhD; Jae-Woo Kwon, MD, PhD; Han-Ki Park, MD, PhD; Hye-Kyung Park, MD, PhD; Sang Hoon Kim, MD, PhD; Jeong-Hee Choi, MD, PhD; Sujeong Kim, MD, PhD; So-Young Park, MD, PhD; et al. (World Allergy Organization Journal, 2024)
Background: Anti-type 2 (T2) biologic therapies (biologics) improve exacerbation rates, lung function, and asthma-related quality of life (QoL) in patients with severe T2 asthma. However, studies comparing different biologics are lacking. We evaluated the QoL in patients with severe asthma comprehensively and compare the efficacy of different T2-directed biologics using QoL questionnaires. Methods: We compared the QoL between severe and mild-to-moderate asthma and between severe asthma with and without biologics treatment. Data of mild-to-moderate were extracted from the Cohort for Reality and Evolution of Adult Asthma in Korea, and data of severe asthma were collected from the Precision Medicine Intervention in Severe Asthma. We included 183 patients with severe asthma treated with T2 biologics or conventional therapy between April 2020 and May 2021 and assessed QoL of them using the Questionnaire for Adult Korean Asthmatics (QLQAKA), Severe Asthma Questionnaire (SAQ), and EuroQoL-5Dimensions (EQ-5D) at baseline and 6 months. Results: The EQ-5D index (0.803) of severe asthma was lower than that of other chronic diseases representing a worse QoL. The scores for all questions of QLQAKA, except “cough,” were lower (less control) in the severe asthma group than in the mild-to-moderate asthma group at baseline and 6 months (P < 0.05). The total scores and subscores of all domains of the QLQAKA, SAQ, and EQ-5D improved significantly 6 months after biologic therapy but not after conventional therapy. The total QLQAKA, SAQ, and EQ-5D scores improved after 6 months in the anti-IL-5 (P < 0.05) and anti-IL-4/IL-13 (P < 0.05) treatment groups with no significant difference between groups (P > 0.05). Conclusion: QoL was worse in severe asthma than in mild-to-moderate asthma and other chronic diseases. T2 biologics equally improved QoL in patients with severe asthma.